Universality of defect-skyrmion interaction profiles - Imara Lima Fernandes (Nature Portfolio, 2018)
Clear understanding of the influence from material inhomogeneities and defects is one of the keys to achieve reliable Skyrmion based devices. Here the authors report their first principles studies on the interaction of single skyrmions with single-atom impurities and reveal its universal shape originated from the defect’s electron filling.